The mRNA‐binding proteome of a critical phase transition during Arabidopsis seed germination. Issue 1 (13th November 2021) - Sajeev, Nikita; Baral, Anirban; America, Antoine H. P.; Willems, Leo A. J.; Merret, Rémy; Bentsink, Leónie
Summary: Arabidopsis thaliana seed germination is marked by extensive translational control at two critical phase transitions. The first transition refers to the start of hydration, the hydration translational shift. The second shift, the germination translational shift (GTS) is the phase between testa rupture and radicle protrusion at which the seed makes the all or nothing decision to germinate. The mechanism behind the translational regulation at these phase transitions is unknown. RNA binding proteins (RBPs) are versatile players in the post‐transcriptional control of messenger RNAs (mRNAs) and as such candidates for regulating translation during seed germination. Here, we report the mRNA binding protein repertoire of seeds during the GTS. Thirty seed specific RBPs and 22 dynamic RBPs were identified during the GTS, like the putative RBP Vacuolar ATPase subunit A and RBP HSP101. Several stress granule markers were identified in this study, which suggests that seeds are prepared to quickly adapt the translation of specific mRNAs in response to changes in environmental conditions during the GTS. Taken together this study provides a detailed insight into the world of RBPs during seed germination and their possible regulatory role during this developmentally regulated process.